Glacier mass balance in the Qinghai–Tibet Plateau and its surroundings from the mid-1970s to 2000 based on Hexagon KH-9 and SRTM DEMs - Zhou, Yushan; Li, Zhiwei; Li, Jia; Zhao, Rong; Ding, Xiaoli (Remote sensing of environment, 2018)
In the context of global warming, glacier changes in the Qinghai–Tibet Plateau (QTP) and its surroundings have attracted a great amount of public attention. To date, there have been many studies of glacier mass balance across the QTP. However, given that most of the previous studies have focused on a short observation period (2000–2015), and that long-term mass change measurements are available only for some local regions, we utilized declassified KH-9 images and 1 arc-second Shuttle Radar Topography Mission (SRTM) digital elevation models (DEMs) to provide the region-wide mass balance (from the mid-1970s to 2000) for a larger scale (including 11 sample regions) across the QTP and its surroundings. The final results indicate that the glaciers in the northwest of the QTP have shown a less negative or near-zero mass balance, ranging from −0.11 ± 0.13 m w.e. a−1 to 0.02 ± 0.10 m w.e. a−1, compared to those in the southeast part, with a mass balance range of −0.30 ± 0.12 m w.e. a−1 to −0.11 ± 0.14 m w.e. a−1. The most serious mass loss has emerged in the central-eastern Himalaya. Integrating our results with the observations after 2000 suggests that, over the past four decades (mid-1970s to the mid-2010s), the glaciers in the Himalaya, Nyainqêntanglha, and Tanggula mountains, as a whole, have exhibited accelerated mass loss, and the most significant acceleration has occurred in the eastern Nyainqêntanglha. Moreover, the Hindu Raj glaciers have shown a stable rate of continuous mass loss, while a nearly stable or slight mass gain state in the western Kunlun region can be dated back to at least as far as the mid-1970s. •Glacier mass balances (1975–2000) in the Tibet Plateau are estimated.•Glaciers in the northwest experienced less ice loss than those in the southeast.•The Himalaya-Nyainqêntanglha glaciers showed accelerated mass loss after 2000.•The western Kunlun glaciers have been in a stable state since the mid-1970s.